Primary renal embryonal rhabdomyosarcoma in an adult patient. Issue 1 (21st January 2020) - Connor, Jessica; Tsui, Johnson F; He, Wenlei; Munver, Ravi
Abstract : Adult renal rhabdomyosarcoma (RMS) is a rare and aggressive entity with a paucity of data and reports in the literature. As a result, treatment guidelines for this malignancy are not well-established. Herein, we present the diagnosis, management and clinical course of a 39-year-old patient diagnosed with primary renal embryonal RMS (ERMS) following radical nephrectomy. We also review the existing literature on primary renal ERMS.